Conditions for a successful transition in Afghanistan post-2014 - Khalid Aziz (Danish Institute for International Studies (DIIS), 2014)
In a new report DIIS Visiting Analyst Khalid Aziz identifies policy areas and measures that need special attention in order to facilitate a healthy transition of Afghanistan after the foreign combat forces have pulled out in 2014. Pointing at the multiple areas in need of transformation he particularly sheds light on the troubled relations between Pakistan and India, the need for ensuring free and fair elections in Afghanistan, the need for implementing good governance and dealing with corruption, the need for reconciliation with the Taliban, the need for strengthening the Afghan national Security forces, and finally the need for ensuring convergence between the Afghan government's plans and policies on the one hand and the conditions of aid provided by the international community on the other.
Keywords: 300